Mechanistic insights into how Azospirillum argentinense Az39 improves nitrogen economy and grain quality in barley independently of chemical fertilization - Caputo, Carla; Gomez, Federico M.; Ciolfi, Federico; Puente, Mariana Laura; Criado, María Victoria (Springer, 2025)
Cereal crops require high nitrogen (N) inputs, but fertilizer use is inefficient, increasing costs and environmental risks. The use of microbial inoculants such as Azospirillum argentinense Az39 and the improvement of N remobilization are promising strategies for improving N use efficiency. We evaluated how A. argentinense Az39 modulates N economy in malting barley under different nutritional conditions, emphasizing N remobilization, post-anthesis uptake, and underlying mechanisms, as well as their combined impact on grain yield and quality. Greenhouse factorial trials combining Az39 inoculation and chemical fertilization demonstrated that Az39 modified the preference of the N source reaching the grain by increasing N remobilization relative to N uptake after anthesis, thereby improving N use efficiency and reducing dependence on soil N after anthesis. This occurred without changing the total N in the shoot, but rather its distribution, as inoculation with Az39 improved N in the leaves, particularly proteins and Rubisco. In addition, N remobilization improved with differentiated contributions from tissues to grain N, with leaves contributing mainly to net N remobilization and stems to remobilization efficiency. Inoculation also improves overall yield but mainly boosted individual grain weight without compromising grain N concentration, probably due to the increased carbohydrate export from leaves. These effects may be associated with high levels of indoleacetic acid in the leaves, which could contribute to both increased leaf N accumulation and improved grain development. Therefore, Az39 represents a valuable tool for sustainable agricultural management, enhancing N remobilization and use efficiency, as well as yield and grain quality in malting barley.